2022
DOI: 10.1038/s41413-021-00176-8
|View full text |Cite
|
Sign up to set email alerts
|

PDGFRα reporter activity identifies periosteal progenitor cells critical for bone formation and fracture repair

Abstract: The outer coverings of the skeleton, which is also known as the periosteum, are arranged in concentric layers and act as a reservoir for tissue-specific bone progenitors. The cellular heterogeneity within this tissue depot is being increasingly recognized. Here, inducible PDGFRα reporter animals were found to mark a population of cells within the periosteum that act as a stem cell reservoir for periosteal appositional bone formation and fracture repair. During these processes, PDGFRα reporter+ progenitors give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…8A), which is consistent with published studies. (31) We further confirmed these observations using FC and found that the proportion of the PDGFRα + cells in the nonhematopoietic and nonendothelial (CD45 À CD31 À ) population was $15-fold higher in the intact bone (devoid of BM) than in the BM (Fig. 8B).…”
Section: Cbd and Cbg Enhance The Biomechanical Properties Of Healed Bonesupporting
confidence: 77%
See 1 more Smart Citation
“…8A), which is consistent with published studies. (31) We further confirmed these observations using FC and found that the proportion of the PDGFRα + cells in the nonhematopoietic and nonendothelial (CD45 À CD31 À ) population was $15-fold higher in the intact bone (devoid of BM) than in the BM (Fig. 8B).…”
Section: Cbd and Cbg Enhance The Biomechanical Properties Of Healed Bonesupporting
confidence: 77%
“…injection of 100 mg/kg tamoxifen (Sigma-Aldrich) for 5 successive days; on the sixth day, the mice underwent the fracture surgeries. (31) At harvest time, the animal was euthanized, and the fractured hindlimb was harvested from the mid-femur to the tibiotalar joint to avoid disturbing the callus tissue. Most of the surrounding soft tissues were removed with care not to disturb the fracture site.…”
Section: Animalsmentioning
confidence: 99%
“… 42 Basal expression of PDGFRα reporter activity is present within multiple cells capable of bone formation, including perivascular adventitial cells, 26 perineural cells, 26 intra-articular, and periarticular ligaments, 27 and in some periosteal cells. 43 Interesting, in our prior work we observed that the frequency of PDGFRα + cells especially within the perivascular space differs somewhat widely across organs. 26 Some vascularized tissue sites are enriched for PDGFRα + adventitial perivascular cells (eg, aorta, skeletal muscle, and adipose tissue), while several visceral sites showed infrequent PDGFRα + adventitial cells (eg, liver and lung).…”
Section: Discussionmentioning
confidence: 84%
“…In this study, we analyzed the CD51 + /PDGFR-α + population in pulp tissue and cultured cells. Previous studies reported that PDGFR-α + cells were increased in the bone marrow of aged mice, whereas PDGFR-α + cells were noted to be critical for bone formation (Maryanovich et al 2018; Xu et al 2022). The influence of chronological aging on PDGFR-α + cells and pulp tissue remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the number of PDGFR-α + and CD51 + cells decreased during chronological senescence. PDGFR-α + cells have been reported to be stem cells/progenitor cells and play a role in tissue repair and regeneration (Maryanovich et al 2018; Xu et al 2022). We observed a decreased self-renewal ability of hDPSCs from aged human pulp.…”
Section: Discussionmentioning
confidence: 99%